Glomerular and Tubular Renal Function after Repeated Once-Daily Tobramycin Courses in Cystic Fibrosis Patients. (4th January 2017) - Stehling, Florian; Büscher, Rainer; Grosse-Onnebrink, Jörg; Hoyer, Peter F.; Mellies, Uwe
Abstract : Introduction . Antibiotic treatment regimens against Pseudomonas aeruginosa lung infection in cystic fibrosis (CF) patients often include aminoglycoside antibiotics that may cause chronic renal failure after repeated courses. Aminoaciduria is an early marker of acute aminoglycoside-induced renal tubular dysfunction. We hypothesized that urinary amino acid reabsorption is decreased after repeated once-daily tobramycin therapies. Methods . In this prospective cross-sectional study creatinine clearance was estimated by the Schwartz and the Cockcroft-Gault formula. Tubular amino acid reabsorption was determined by ion exchange chromatography in 46 patients with CF who received multiple tobramycin courses (6.3 ± 10.1 (1–57)) in a once-daily dosing regimen and 10 who did not. Results . Estimated creatinine clearance employing the Cockcroft-Gault was mildly reduced in 17/46 (37%) of the patients who received tobramycin and 5/10 (50%) of the patients who did not but in none using the Schwartz formula. No association with lifetime tobramycin courses was found. Tubular amino acid reabsorption was not influenced by the amount of once-daily tobramycin courses. Conclusion . Clinically not significant reduction of eCCL occurred in a minority of CF patients. However, chronic tubular dysfunction was not present in patients with CF repeatedly treated with tobramycin in the once-daily dosing scheme.